1988
DOI: 10.1111/j.1471-4159.1988.tb01818.x
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Modulation of [3H]MK‐801 Binding to the N‐Methyl‐d‐Aspartate Receptor‐Ion Channel Complex by l‐Glutamate, Glycine, and Polyamines

Abstract: In extensively washed rat cortical membranes [3H](+)-5-methyl-10,11-dihydro-5 H-dibenzo [a,d]cyclohepten-5,10-imine ([3H]MK-801) labeled a homogeneous set of sites (Bmax = 1.86 pmol/mg protein) with relatively low affinity (KD = 45 nM). L-Glutamate, glycine, and spermidine produced concentration-dependent increases in specific [3H]MK-801 binding due to a reduction in the KD of the radioligand. In the presence of high concentrations of L-glutamate, glycine, or spermidine, the KD values for [3H]MK-801 were reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
349
1
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 747 publications
(362 citation statements)
references
References 20 publications
11
349
1
1
Order By: Relevance
“…Zn ++ blocks the channel in a voltage-independent manner 3 2 0 , whereas the polyamine site 3 2 1 , 3 2 2 binds compounds such as spermine or spermidine, either potentiating 321,322 or inhibiting 322 the activity of the receptor. Potentiation or inhibition depends on the combination of subunits forming each NMDA receptor 322 .…”
Section: ) Synaptic Plasticitymentioning
confidence: 99%
“…Zn ++ blocks the channel in a voltage-independent manner 3 2 0 , whereas the polyamine site 3 2 1 , 3 2 2 binds compounds such as spermine or spermidine, either potentiating 321,322 or inhibiting 322 the activity of the receptor. Potentiation or inhibition depends on the combination of subunits forming each NMDA receptor 322 .…”
Section: ) Synaptic Plasticitymentioning
confidence: 99%
“…Brain membranes were prepared according to the method described by Ransom and Stec (28). TK40 was dissolved as a 1 mM stock solution in 50% DMSO-water.…”
Section: Dna Constructs and Expression In Xenopusmentioning
confidence: 99%
“…It has been shown that some polyamines (e.g. , spermine and spermidine) can alter the activ ity of NMDA receptors (Ransom and Stec, 1988) and protamine may have a similar effect. The lack TABLE 2.…”
Section: Discussionmentioning
confidence: 99%